Influence of Diabetes Mellitus on the Incident of Stroke: Meta-Analysis - Mubarok, Ahmad Syauqi; Kurniawan, Hendra Dwi; Verasita, Prissy; Azmiardi, Akhmad; Puspitasary, Kiky (Indonesian Journal of Global Health Research, 2023)
Blood vessel disorders can occur due to the narrowing and hardening of the artery walls, which is called atherosclerotic plaque. Stroke is a serious health problem because of the high mortality and morbidity rates and its impact can cause chronic disability and occurs not only in elderly people but also in young people. This study aims to estimate and analyze the effect of diabetes mellitus on the incidence of stroke. This research is a systematic review and meta-analysis research using the PRISMA diagram. Article searches were carried out based on the PICO Model eligibility criteria. P= DM patient; I= Diabetes mellitus; C= Normal blood sugar; O= Stroke. The articles used come from Google Scholar. With keywords including "Diabetes mellitus" AND "Normal blood sugar" AND "Stroke" AND "adjusted Odds Ratio". Articles were analyzed using the PRISMA diagram and the Review Manager 5.3 application. 5 articles (2016-2022) with a randomized controlled trial study design will be used as a source for meta-analysis of the effect of diabetes mellitus on the incidence of stroke. Shows that people with diabetes mellitus increase the likelihood of stroke. Patients suffering from diabetes mellitus increase the likelihood of stroke by 2.41 times compared to those with normal blood sugar. (aOR= 2.41; 95% CI= 1.71 to 3.39; p=0.0001), and statistically significant. The forest plot also shows high heterogeneity of effect estimates between studies (I2 = 73%). The funnel plot shows that there is publication bias which tends to exaggerate the true effect (overestimate). Meta-analysis of 5 studies cross-sectional concluded that people with diabetes mellitus increase the likelihood of stroke.